2012
DOI: 10.1016/j.aop.2011.11.010
|View full text |Cite
|
Sign up to set email alerts
|

An explanation of interference effects in the double slit experiment: Classical trajectories plus ballistic diffusion caused by zero-point fluctuations

Abstract: A classical explanation of interference effects in the double slit experiment is proposed. We claim that for every single "particle" a thermal context can be defined, which reflects its embedding within boundary conditions as given by the totality of arrangements in an experimental apparatus. To account for this context, we introduce a "path excitation field", which derives from the thermodynamics of the zero-point vacuum and which represents all possible paths a "particle" can take via thermal path fluctuatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(87 citation statements)
references
References 26 publications
(58 reference statements)
2
82
0
Order By: Relevance
“…2.2). In our emergent quantum mechanics approach, we have given a superclassical explanation of interference effects at a double slit [12], thereby arriving at expressions for the probability density current and the corresponding velocity field completely equivalent to the guidance equation, which is the central postulate of the de Broglie-Bohm interpretation [21,22]. Our claims, to be substantiated in this paper, consist in the assertion that the guidance equation is of some "invisible hand" type, i.e.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…2.2). In our emergent quantum mechanics approach, we have given a superclassical explanation of interference effects at a double slit [12], thereby arriving at expressions for the probability density current and the corresponding velocity field completely equivalent to the guidance equation, which is the central postulate of the de Broglie-Bohm interpretation [21,22]. Our claims, to be substantiated in this paper, consist in the assertion that the guidance equation is of some "invisible hand" type, i.e.…”
Section: Introductionmentioning
confidence: 92%
“…In particular, with the dynamics between the oscillator on the one hand, and the "bath" of its thermal environment as constrained by the experiment's boundary conditions on the other hand, one can explain not only Gaussian diffraction at a single slit [15], but also the well-known interference effects at a double slit [12,27]. As already mentioned, we have also shown that the spreading of a wave packet can be exactly described by combining the convective with the orthogonal diffusive velocity fields.…”
Section: A Superclassical Derivation Of the Guidance Equationmentioning
confidence: 99%
See 3 more Smart Citations